The association of 24-hour behavior rhythms with stroke among American adults with prediabetes/diabetes: evidence from NHANES 2011-2014 - Wenbo Gu; Zhen Tian; Wanying Hou; Yi Yang; Yifan Ma; Yuhua Song; Haixin Wang; Changhao Sun (BMC, 2024)
Abstract Background Emerging evidence suggests that circadian rhythms play a role in the regulation of cardiovascular diseases (CVDs). We aim to examine the relationship between the 24-hour behavior rhythms (activity-rest and feeding-fasting rhythms) and stroke. Methods The study included 3201 adult participants with prediabetes/diabetes from the National Health and Nutrition Examination Survey (NHANES) 2011-2014. The 24-hour behavior rhythm indices were calculated using data from accelerometer wearable device and dietary recall for two nonconsecutive days. Six indices were calculated including interdaily stability (IS), intradaily variability (IV), relative amplitude (RA), average activity during the least active continuous 5-hour period (L5), Average activity during the most active continuous 10-hour period (M10) which reflects the activity-rest rhythm, and feeding rhythm score which reflects the feeding-fasting rhythm. These continuous variables were divided into quintiles for logistic regression models. Results Comparing participants in quintile 1, those in quintile 5 of IS and RA exhibited a lower odds of stroke. Conversely, participants in quintile 5 of IV, L5, and L5 start time demonstrated a higher odds of stroke. Furthermore, participants in quintile 5 of feeding rhythm score had a significantly lower odds of stroke. The associations of IV and feeding rhythm score with stroke were more pronounced in participants with diabetes compared to those with prediabetes/diabetes. No significant associations were observed between other 24-hour behavior rhythms and stroke. Conclusions Overall, this study highlights a significant association between 24-hour behavior rhythm and stroke in American adults with prediabetes/diabetes.